Rekonstruksi Konsep Keseimbangan Pasar dalam Perspektif Mikro Ekonomi Syariah - Helisia Krisdayanti; Citra Pertiwi; Aziz Septiatin; Citra Lestari (INDO PUBLISHING, 2026)
This study aims to reconstruct the concept of market equilibrium from the perspective of Islamic microeconomics by reexamining the principles of demand, supply, and price mechanism through the lens of justice, ethics, and the objectives of Islamic law (maqāṣid al-sharī‘ah). In conventional economics, market equilibrium is achieved through the free interaction between demand and supply, often neglecting moral considerations and equitable distribution. In contrast, Islamic economics conceptualizes market equilibrium not merely as the meeting point of quantities demanded and supplied but as a condition that ensures fairness, transparency, and the avoidance of riba, gharar, and ihtikār (hoarding). Using a qualitative approach based on literature analysis, this study finds that reconstructing the concept of market equilibrium requires integrating natural market mechanisms with ethical regulations derived from Islamic values. The findings indicate that market equilibrium in Islam is dynamic, socially oriented, and capable of creating a competitive, stable, and just market structure.